IMD307: Reference and Information Services for Information Agencies / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course is an introduction to reference and information services in information agencies. Students are exposed to the techniques of reference activities and reference sources used in any information agencies and how to assist user in seeking information.